Capacity Development for Civil Society Organizations: Selected Cases in the Philippines - Bismonte, Candice Elaine B. (Animo Repository, 2014)
This study looked into the capacity development interventions of three selected organizations in the Philippines that participated in a larger project on strengthening CSOs funded by an international aid agency. This study specifically examined the factors that may influence capacity development interventions, namely, organizational profile and external factors. Furthermore, it also explored how capacity development interventions can influence organizational effectiveness. Using the triangulation approach, this study made use of both qualitative and quantitative methods. It specifically utilized key informant interviews, documents review, and capacity assessment tool. The three selected CSOs represent the three major geographical areas of the Philippines, Luzon, Visayas, and Mindanao. Results indicated that the knowledge, skills, experience and engagement of the Board and Management are important in carrying out their Governance and Leadership functions that are essential in the success of implementing changes geared to develop and effectively manage the organization. In support of Board and Managements leadership, financial and human resources are necessary means to implement changes and operate effectively. Mentoring is a key component among the capacity development interventions as it provides more focused and specified assistance to the CSOs rather than generic interventions targeting different types of organizations with various needs. Capacity development interventions (CDI) also produced unintentional gains like providing a venue for participants to learn from and inspire each another and to be able to network and link with other organizations and individuals that can be sources of future opportunities. The project, its interventions including the mentors provided input and served as facilitators and partners in the capacity development but ultimately, the success or how well the organization will actually progress is dependent on how CSOs will maximize the benefits of the interventions by converting them into actual output and translating them to concrete corrective actions. Funding opportunities or financial assistance can be incentives or motivation for the CSOs to give time, effort and priority in putting their systems in place. Backroom operations like administrative, personnel and financial management are as important as program activities. Good housekeeping and internal management of all the areas of an organization affect how external entities view them as an effective and trusted partner. The organizational profiles provided the background and context of the CSOs but self-assessment provided more in-depth data on gaps and needs that serves as reference on what appropriate capacity development interventions will be undertaken.